Análise do período de espera do diagnóstico ao primeiro tratamento do câncer de mama - Castro, Francine Coutinho Maia de (2019)
Breast cancer presents the second highest cancer incidence rate in Brazil and in the world. In addition, it’s the greatest worldwide cause of cancer mortality in women. In this context, the treatment waiting time is a concern in many regions. Thus, this thesis provides an integrated review about the effect of therapeutic delay on the clinical progression of breast cancer, which showed, through the analysis of 22 articles published between 2013 and 2018, that waiting times over 60 days are associated with higher rates of local and regional recurrence, as well as metastatic disease. In addition, it was observed that Brazil has longer waiting times than other countries. We also carried out a analytical retrospective study of 118 cases at the Hospital Universitário de Santa Maria (HUSM), from January 1, 2012 to December 31, 2016, which showed an average waiting time for the 1st breast cancer treatment of 104.4 days and a median of 92,5 days, 66,9% of which waited more than 60 days, the limit recommended by Brazilian Law No. 12,732, of November, 2012. In addition, 85.2% of the cases whose treatment began with surgery exceeded the limit of 60 days, while 67.6% of the cases treated with neoadjuvant chemotherapy started therapy in a timely manner. We believe that this significant delay for surgery is associated to precarious hospital infrastructure. No statistically significant results were found related to the influence of the delay on cancer progression. In conclusion, the limit of 60 days imposed by the Ministry of Health is an appropriate recommendation, since therapeutic delay contributes to the cancer progression, according to the literature. However, further studies during a longer period and with a greater number of cases are needed at HUSM to clarify the results found. It is hoped that this research will encourage further research to stimulate the creation of public health policies aimed at increasing the hospital structure. This way it is hoped to reduce inequities in the care of patients and providing timely oncological treatment to avoid an aggravation of clinical conditions.